Combined cataract surgery and aniridia ring implantation in oculocutaneous albinism. Issue 11 (November 2015) - Farahi, Azadeh; Hashemi, Hassan; Mehravaran, Shiva
Abstract : Purpose : To present results of cataract surgery combined with aniridia ring implantation in patients with oculocutaneous albinism (OCA) in terms of vision, refraction, eye movements, and subjective photophobia and glare. Setting : Anterior segment services of Noor Eye Hospital, Tehran, Iran. Design : Consecutive clinical case series study. Methods : Enrolled patients underwent phacoemulsification and posterior chamber intraocular lens (PC IOL) implantation and had 2 Morcher aniridia rings (types 50 F or 50 E) inserted intracapsularly. Preoperative and postoperative examinations included tests for visual acuity, manifest refraction, measurement of ocular alignment, and electronystagmography. After surgery, patients also completed a questionnaire to subjectively assess glare reduction. Results : Twelve eyes of 6 OCA patients were included. Minimum follow‐up was 6 months. None of the patients had any intraoperative or postoperative complications. In addition to improved uncorrected and corrected distance visual acuity and significant reduction of refractive error, all patients had a marked reduction of glare and photophobia after surgery. Conclusion : Iris ring implantation during cataract surgery was an effective procedure for increasing vision and reducing glare disability in patients with OCA. In light of the results and patients' expressed satisfaction, a study should be performed to assess the outcomes of refractive lens exchange along with implantation of a PC IOL and prosthetic iris device in OCA patients seeking refractive correction.